2017
DOI: 10.1002/pc.24607
|View full text |Cite
|
Sign up to set email alerts
|

“Green” composites using bioresins from agro‐wastes and modified sisal fibers

Abstract: Green" composites were fabricated using modified sisal fibers and agro-waste derived resins from nonedible protein and starch in a simple and cost-effective manner. Sisal fibers were modified using a novel combination of mercerization followed by heat treatment under a pre-determined tension which improved their Young's modulus by over 200% (from 5.5 to 16.7 GPa) and tensile strength by about 50% (from 300 to 450 MPa). The non-edible protein and starch were extracted from defatted karanja (Pongamia pinnata) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 43 publications
(73 reference statements)
0
9
0
1
Order By: Relevance
“…Stem fiber, leaf fiber, and seed fiber are the three main fibers [ 20 ]. The most common natural fibers are hemp, doum, coir, jute, almond shells, rice husk, oat husk, wheat straw, switchgrass, corona, kenaf, coconut, bamboo, bagasse, banana, sisal, sugarcane, oil palm empty fruit bunch [ 20 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stem fiber, leaf fiber, and seed fiber are the three main fibers [ 20 ]. The most common natural fibers are hemp, doum, coir, jute, almond shells, rice husk, oat husk, wheat straw, switchgrass, corona, kenaf, coconut, bamboo, bagasse, banana, sisal, sugarcane, oil palm empty fruit bunch [ 20 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Moreover, numerous research studies on the development of waste-filled composites demonstrated that these products could be an efficient solution not only to the plastic disposal problem but also to waste utilization that is either land-filled or incinerated. [5,6] Wood industry plays an important role in the economy of any country and it was reported to produce a total of 270 billion USD in 2018 globally. [7] However, the extraction of useful wood generates nearly 14.1 million tons of solid waste per year by the wood industry.…”
Section: Introductionmentioning
confidence: 99%
“…The annual production volume of natural fibres in Europe in the same year equaled about 315,000 tonnes, and, owing to their promising properties, the European production volume of natural fibre-based composites is likely to more than double by 2020 [ 4 ]. Of all industries, the automotive sector is probably the biggest promoter, user, and developer of green composites [ 3 , 5 , 6 , 7 ]. Above all, the automotive sector is continuously trying to improve the fuel efficiency of vehicles.…”
Section: Introductionmentioning
confidence: 99%